К расшифровке жизненного цикла плягиопоруса Скрябина - Plagioporus skrjabini Kowal, 1951 (Trematoidea, Opecoelidae) - Комарова, Т.И. (Вестник зоологии, 1968)
In the body cavity of Pontogammarus robustoides from the reservoirs of the Danube delta the metacercarii Plagioporus skrjabini were found. For specification of these metacercarii Neogobius kessleri, N. fluviatilis were infected. Seven days after the infection the marita Plagioporus skrjabini was found in bowels of this fish. The first intermediate host is still unknown for the present.